2016
DOI: 10.1038/srep28290
|View full text |Cite
|
Sign up to set email alerts
|

IgE-mediated enhancement of CD4+ T cell responses requires antigen presentation by CD8α− conventional dendritic cells

Abstract: IgE, forming an immune complex with small proteins, can enhance the specific antibody and CD4+ T cell responses in vivo. The effects require the presence of CD23 (Fcε-receptor II)+ B cells, which capture IgE-complexed antigens (Ag) in the circulation and transport them to splenic B cell follicles. In addition, also CD11c+ cells, which do not express CD23, are required for IgE-mediated enhancement of T cell responses. This suggests that some type of dendritic cell obtains IgE-Ag complexes from B cells and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
(104 reference statements)
3
24
0
Order By: Relevance
“…Therefore we and others believe that CD23-expressing B cells likely act as carriers of IgE-immune complexes, which regulate IgE-dependent T-cell activation. 18,19,21 On the other hand, CD23 could also be understood as a decoy receptor for IgE-immune complexes, taking IgE away from the serum and from allergic effector cells. The outcome would still be that CD23 counteracts the allergic pathway to prevent sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we and others believe that CD23-expressing B cells likely act as carriers of IgE-immune complexes, which regulate IgE-dependent T-cell activation. 18,19,21 On the other hand, CD23 could also be understood as a decoy receptor for IgE-immune complexes, taking IgE away from the serum and from allergic effector cells. The outcome would still be that CD23 counteracts the allergic pathway to prevent sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Furthermore, it has been shown that CD23 facilitates induction of antibody and T-cell responses. [18][19][20][21][22] IgE binding to its 2 primary receptors, FcεRI and CD23, is uniquely regulated by dynamic IgE structure-receptor relationships, whereas direct interaction between the 2 receptors through IgE molecules is prohibited by reciprocal allosteric inhibition. [23][24][25][26][27] This cross-inhibition is thought to be regulated by conformational plasticity of the IgE antibody, which can adopt 2 conformational states.…”
mentioning
confidence: 99%
“…was previously shown in the context of allergen-specific IgE. 31,32 However, given the fact that much of the IgE in STAT3-HIES patients does not appear to be allergen-specific, 17 HIES patient B cells did not produce more IgE than control B cells in these conditions, and it is interesting to note that the difference in antibody production between STAT3-HIES and controls in response to CD40L + IL-4 + IL-21 was smaller for IgE than for most other isotypes. This indicates that CSR to IgE is less severely impaired than CSR to most other isotypes.…”
Section: Reduced Immunoglobulin Heavy Chain Variable Region Gene Shmentioning
confidence: 73%
“…In a mouse model, a similar interaction of B cells and DCs has already been proposed. 40 To better understand the interactions of B cells and dendritic cells in humans, further studies are required, especially on the importance of DC subsets and on the B cell-derived signals that are inducers of costimulators. Furthermore, the uptake of IgE-ICs by DCs may not always be mediated by CD23 but also by FcεRI, which has been shown to be expressed in certain types of DCs.…”
Section: Discussionmentioning
confidence: 99%